La loi du 3 janvier 1979 et le traitement des documents postérieurs à 1940 - Gut, Christian (Gazette des archives, 1979)
The Archive Law of 3 January 1979 and the arrangement of documents posterior to 1940. The official "arrangement schedule" for departmental archives in France is closed at the year 1940. Opinions of archivists differ as to the advisability to extend this schedule (fïrst elaborated in 1841) to documents posterior to 1940, to give them a corresponding system of numbering, and to maintain for them the traditional " répertoires " (summary lists). Many of them seem to wish a simplification of the existing system and a more pragmatic approach in this field.

La loi du 3 janvier 1979 (France) et le traitement des documents postérieurs à 1940 - Gut, Christian (La Gazette des archives, 1979)

Manuel d'archivistique. Théorie et pratique des Archives publiques en France - Association des archivistes français (AAF) (1970)